PREVENTION OF INTELLECTUAL AND MNESTIC DISORDERS IN IODINE DEFICIENCY AMONG PRESCHOOL CHILDREN - A.A. Dzhumagaziev; M.V. Bogdan'yants; N.G. Kosmacheva; D.A. Bezrukova; S.F. Aryukova (Union of pediatricians of Russia, 2007)
The researchers diagnosed the state of the optic and motor functions and intelligence among 107 preschool children (average age - 6,5 years old) in 4 different educational institutions of Astrakhan' where according to the findings they noted the moderate iodine deficiency. They also disclosed the central nervous system functional disorders which manifest themselves through the absent mindedness, insufficient concentration and purposefulness, psychic and emotional disorder. The daily iodine intake of 100 micrograms for 6 months had a positive effect on the acceleration of the preschool children's psychic and motor growth.Key words: iodine deficiency, children, central nervous system functional disorders.